A follow up study of alcohol dependent patients following in patient treatment at the Avalon Treatment Centre - Dirks, Bryan Larry (Department of Psychiatry and Mental Health, 2017)
This is a report of an investigation assessing outcome in a consecutive series of alcohol dependent patients admitted to the Avalon Treatment Centre from 21 October 1985 to 14 April 1986. Although extensive work has been done on the epidemiology of alcoholism among "coloured" people * [classified in terms of the population registration Act]. A direct result of the original field survey by Gillis, Keet and Slabbert was the establishment of this centre. A follow up study of people identified as having drinking problems in the original field survey showed that few people stopped drinking on their own account. Little is known about treatment outcome of patients hospitalized at this centre. Treatment at The Avalon Treatment Centre is based on therapeutic community principles, group therapy, family and social case work as well as the use of antabuse. Contact with Alcoholics Anonymous is encouraged during and after hospitalisation. In addition patients are also followed up by a community sister.